PENGARUH PERTUMBUHAN EKONOMI TERHADAP TINGKAT PENGANGGURAN TERBUKA DI KOTA BINJAI TAHUN 2018-2022 - nataliani br sitepu, Devi; Samri Juliati Nasution, Yenni (Jurnal Ekonomi STIEP, 2023)
In order to determine whether and how economic growth influences the open unemployment rate in Binjai from 2018 to 2022, the study will look at whether there is an effect on it. According to this view, economic growth is the process of enhancing a nation's ability to produce goods and services through its economic activities. One issue that frequently impedes economic growth is a decline in the ratio of job seekers to government- or privately-provided positions. This essay employs a quantitative descriptive analysis approach and a straightforward linear regression technique with SPSS 22 to address the research problems. There is no positive or significant relationship between economic growth and the open unemployment rate in Binjai City, as evidenced by the test results, which yield a t test value of t count (-1.321) t table (3); H0 is accepted; and Sig (0.278) > 0.05. Remember that only 36.8% of Binjai's open poverty rate is affected by economic growth, with the remaining 63.2% being affected by unmentioned causes.